1984
DOI: 10.1159/000215066
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Neutralization during Collection and Processing of Blood Inhibited by Pyridoxal 5′-Phosphate

Abstract: Spectrophotometric heparin assays are expected to be independent on clotting factors, either activated or nonactivated, but could be sensitive to heparin neutralization during blood collection. Is was shown that more than 200 U of heparin/1 plasma can completely be neutralized during blood processing. Because the heparin neutralization is not constant but dependent on the sample as well as on the type of sample handling, one cannot beforehand compensate and correct the results for possible heparin neutralizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This represents a heparin concentration that in rigor ously platelet and PF 4 free plasma will cause more then 95% inhibition of thrombin formation (15). It has been shown that mere venipuncture, if carried out under routine conditions, induces platelets to produce a quantity of heparin neutralizing material equivalent to 0.183 ± 0.067 U/ml of heparin (22). The amount of heparin neutralized in our experiments, in which platelets were maximally triggered with Ca-ionophore, therefore does not seem to be unrealistically high.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…This represents a heparin concentration that in rigor ously platelet and PF 4 free plasma will cause more then 95% inhibition of thrombin formation (15). It has been shown that mere venipuncture, if carried out under routine conditions, induces platelets to produce a quantity of heparin neutralizing material equivalent to 0.183 ± 0.067 U/ml of heparin (22). The amount of heparin neutralized in our experiments, in which platelets were maximally triggered with Ca-ionophore, therefore does not seem to be unrealistically high.…”
Section: Discussionmentioning
confidence: 48%
“…We postulate that this retardation is instrumental in obtaining an antithrombo tic effect with low doses of heparin. On basis of the data of van Putten et al (22) we can assume that a circulating heparin concentration of 0.1-0.2 U/ml will hardly be detected by routine laboratory methods. This accounts for the difficulty in finding a laboratory correlate to the antithrombotic action of low dose heparin.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin binds to numerous plasma substances (4,(12)(13)(14)(15). Utilizing various techniques, others have demonstrated consider able quantities of masked heparin (3,5,15). The technique described here is simple, can be applied to blood samples collected with any anticoagulation technique, and will unmask any exogenous heparin added to plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The APTTs of plasmas obtained at 600 x g were slightly shorter than those obtained at 940 x g and 2200x g. This difference might be due to a higher platelet concentration in the Storage conditions had considerable influence on the APTT, Both shortening and lengthening of APTT was observed. Shortening of APTT may be due to in vitro release of heparin neutralizing activity from platelets, as has been suggested by several other authors (7,10,11). Lengthening may be due to inactivation of labile clotting factors like Factor V and Factor VIII.…”
Section: Aptts Of Healthy Persons Obtained In Our Laboratory (Thble 1)mentioning
confidence: 59%